ANALISIS PENGARUH TENAGA KERJA TERDIDIK, TENAGA KERJA TIDAK TERDIDIK, DAN REALISASI BELANJA MODAL PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI (Studi Kasus: Barlingmascakeb, Subosukawonosraten, Dan Kedungsepur) - Bachtiar, Philip Ali; Sugiyanto, FX (Diponegoro Journal of Economics, 2013)
Three regionalization in Central Java which have a big region is Barlingmascakeb, Subosukawonosraten, and Kedungsepur.each regionalization be expected to colaborate for more equatable development. The purpose of this research is making estimation about the role of Educated and Uneducated Labor, and also Realization of Government Capital Expenditure related to economic growth in three regionalization. The other reason is describing the growth patern of three regionalization. The method of research uses economic development theory of Cobb – Douglas. Regression analysis is used Least Square Dummy Variables with the help of software EViews 6.This research show that the improvement of economic growth in Barlingmascakeb depend on educated labor and realization of government capital expenditure, but uneducated labor has a negative effect. Whereas, improvement of economic growth in Subosukawonosraten depend on Educated and Uneducated Labor. However, realization of government capital expenditure in Subosukawonosraten has negative effect to economic growth. Whereas, improvement of economic growth in Kedungsepur isn’t depend on educated labor. uneducated labor and realization of government, because the three independent variables has negative effect to economic growth. For the growth patern, Barlingmascakeb and Subosukawonosraten are on low growth and low income category, while Kedungsepur is on high income but low growth category.